Cardiovascular response to exercise training in the systemic right ventricle of adults with transposition of the great arteries - Shafer, K M (J Physiol, 2015)
We aimed to assess the haemodynamic effects of exercise training in transposition of the great arteries (TGA) patients with systemic right ventricles (SRVs). TGA patients have limited exercise tolerance and early mortality due to systemic (right) ventricular failure. Whether exercise training enhances or injures the SRV is unclear. Fourteen asymptomatic patients (34 ± 10 years) with TGA and SRV were enrolled in a 12 week exercise training programme (moderate and high-intensity workouts). Controls were matched on age, gender, BMI and physical activity. Exercise testing pre- and post- training included: (a) submaximal and peak; (b) prolonged (60 min) submaximal endurance and (c) high-intensity intervals. Oxygen uptake ([Image: see text](;) Douglas bag technique), cardiac output ([Image: see text], foreign-gas rebreathing), ventricular function (echocardiography and cardiac MRI) and serum biomarkers were assessed. TGA patients had lower peak [Image: see text], [Image: see text], and stroke volume (SV), a blunted [Image: see text]/[Image: see text] slope, and diminished SV response to exercise (SV increase from rest: TGA = 15.2%, controls = 68.9%, P < 0.001) compared with controls. After training, TGA patients increased peak [Image: see text] by 6 ± 8.5%, similar to controls (interaction P = 0.24). The magnitude of SV reserve on initial testing correlated with [Image: see text] training response (r = 0.58, P = 0.047), though overall, no change in peak [Image: see text] was observed. High-sensitivity troponin T (hs-TnT) and N-terminal prohormone of brain naturetic peptide (NT pro-BNP) were low and did not change with acute exercise or after training. Our data show that TGA patients with SRVs in this study safely participated in exercise training and improved peak [Image: see text]. Neither prolonged submaximal exercise, nor high-intensity intervals, nor short-term exercise training seem to injure the systemic right ventricle. KEY POINTS: Patients with transposition of the great arteries (TGA) and systemic right ventricles have premature congestive heart failure; there is also a growing concern that athletes who perform extraordinary endurance exercise may injure the right ventricle. . Therefore we felt it essential to determine whether exercise training might injure a systemic right ventricle which is loaded with every heartbeat. . Previous studies have shown that short term exercise training is feasible in TGA patients, but its effect on ventricular function is unclear. . We demonstrate that systemic right ventricular function is preserved (and may be improved) in TGA patients with exercise training programmes that are typical of recreational and sports participation, with no evidence of injury on biomarker assessment. . Stroke volume reserve during exercise correlates with exercise training response in our TGA patients, identifying this as a marker of a systemic right ventricle (SRV) that may most tolerate (and possibly even be improved by) exercise training. .